Evaluación de la suplementación del silo de bagazo de caña amonificado con melaza vs maíz molido en vacas mestizas - Anchundia Menéndez, Janell Andrea (2025)
This study aimed to evaluate the impact of ammoniated sugarcane bagasse silage, combined with molasses or ground corn, on the production and health of crossbred dairy cows. The trial involved cows in their second lactation period, using two animals per treatment with a total of eight replications. The cows were distributed across four treatments: T1 (bagasse + molasses), T2 (bagasse + ground corn), T3 (bagasse + molasses + 5% urea), and T4 (bagasse + corn + 5% urea). A completely randomized design (CRD) was used, and bromatological variables, milk production, and milk urea levels were measured. In terms of bromatological composition, T3 showed the highest crude protein content (43.65%) with a p-value ≤ 0.016, while T2 had the lowest fiber concentration (NDF: 38.37%) with p ≤ 0.015, and the highest organic matter content (96.89%) with p ≤ 0.004, indicating greater digestibility. Regarding milk production, T3 was the most prominent treatment on day 3 with 8.75 L/day. However, on day 6, a significant difference was observed (p ≤ 0.015), with T3 (8.38 L/day) and T2 (7.63 L/day) outperforming the other treatments. As for milk urea levels, a significant difference was also found (p ≤ 0.015), with T3 reaching a concentration of 18.70 mg/dL, exceeding the physiological limit, while T4 (16.65 mg/dL) presented a more acceptable level. These results suggest that ammoniation with urea enhances the nutritional value of bagasse and that its combination with molasses or corn has distinct effects on milk production and cow metabolism.